Anchor placement and subsequent movement in a mesh kit with self‐fixating tips: 6‐month follow‐up of a prospective cohort. (13th January 2014) - Brennand, EA; Bhayana, D; Tang, S; Birch, C; Murphy, M; Cenaiko, D; Ross, S; Robert, M
<x xml:space="preserve">Abstract</x> Objective To describe the initial placement of Elevate single‐incision mesh kit device tips relative to the sacrospinous ligament, and to measure tip movement over a 6‐month period from initial placement. Design Prospective cohort. Setting Tertiary care urogynaecology centre in Calgary, Canada. Population Women electing for surgical management of anterior vaginal wall prolapse. Methods Ten women underwent anterior prolapse repair using the Elevate single‐incision mesh kit with a metallic fiducial marker attached to the tips of the surgical device. Women were imaged by magnetic resonance imaging (MRI) within 48 hours of surgery, and again 6 months later to investigate the position of the device tips and change ≥4 mm over the 6‐month postoperative period. Main outcome measure(s) Position of self‐fixating tips within 48 hours of surgery, and at six months post‐operative. Results Anchor insertion was directly into the sacrospinous ligament in 10 of 20 insertion points (50%, 95% CI 27–73%). Movement was most often noted in the cranial‐caudal direction: a change in location of ≥4 mm was observed for 8/20 anchors (40%, 95% CI 19–64%). Cranial‐caudal movement was observed less frequently among sacrospinous anchors than among anchors inserted into other pelvic structures (1/10 versus 7/10, P = 0.020, difference in proportion −60%, 95% CI −94 to −26%). PFDI‐20 scores improved statistically significantly by 6 months (P = 0.008, mean change −62.9%, 95% CI −105.1 to −20.7%), but PFIQ‐7 scores did not change statistically significantly over the same time period (P = 0.523, mean change −12.4%, 95% CI −54.5 to 29.8%). Conclusions The novel self‐fixating anchoring tips of this single‐incision mesh kit do not reliably anchor into the sacrospinous ligament. The tips have been shown to move with time, although not all cases of anchor movement were associated with recurrent prolapse.